Detection of the gas–liquid two-phase flow regimes using non-intrusive microwave cylindrical cavity sensor - Oon, C.S.; Ateeq, M.; Shaw, A.; Wylie, S.; Al-Shamma'a, A.; Kazi, S.N. (Brill Academic Publishers, 2016)
Gas–liquid two-phase flow phenomenon occurs in various engineering applications and the measurement of it is important. A microwave sensor in the form of a cylindrical cavity has been designed to operate between 5 and 5.7 GHz. The aim is to analyse a two phase gas–liquid flow regime in a pipeline. LabVIEW software is utilised to capture the data, process them and display the results in real time. The results have shown that the microwave sensor has successfully detected the two-phase flow regimes in both the static and dynamic flow environments with reasonable accuracy. The study has also shown the independence of the technique and its accuracy to the temperature change (28–83 °C). Several flow regimes of the gas–liquid two-phase flow have been discussed. The system is also able to detect the stratified, wavy, elongated bubbles and homogeneous flow regimes.